Os afetos (sentimentos) podem ser influenciados pela disponibilidade de apoio social em pessoas idosas da comunidade? - Silva, Livia Mazzulli Moreira da (Universidade Federal de São Carlos, 2025)
Social support plays a fundamental role in maintaining mental health, directly influencing the psychological and emotional well-being of elderly people. In terms of feelings and emotions, social support directly influences the quality of emotions experienced. Thus, this research aimed to verify whether there is a relationship between social support and feelings in elderly people in the community. This is a descriptive, cross-sectional study, based on the quantitative research method. The sample consisted of elderly people registered in five Family Health Units in the city of São Carlos, São Paulo, living in areas of high social vulnerability. The instruments used for data collection were: Participant Sociodemographic Characterization Form, Medical Outcomes Study (MOS) Social Support Scale and Portuguese Scale of Positive and Negative Affects Short Form. The data obtained were entered into a database in the Statistical Package for Social Sciences (SPSS) for Windows program to perform descriptive and correlational statistical analyses. The sample consisted of elderly individuals with a mean age of 69.80 years (SD = 6.90), 3.19 years of schooling (SD = 2.92), and individual and family incomes of less than 1.3 and 2.6 minimum wages, respectively. Participants were predominantly female (54.7%, n = 52), married (92.6%, n = 88), brown (49.5%, n = 47), Catholic (51.6%, n = 49), practicing a religion (74.7%, n = 71), retired (77.9%, n = 74), and with a perception of insufficient income (57.9%, n = 55). The mean total social support score was 81.35 points (SD=17.17) and the mean positive and negative affect scores were 13.58 points (SD=4.37) and 9.20 points (SD=4.09), respectively. Among the results, we highlight the directly proportional correlations between the total social support scores and the positive affect (rho=0.396, p=0.000) and the specific “inspired” affect (rho=0.306, p=0.003). It is concluded that elderly people with a better perception of the availability of social support have more positive affects (feelings).
Can affects (feelings) be influenced by the availability of social support in community-dwelling older adults?
Keywords: Apoio social; Emoções; Idoso; CIENCIAS DA SAUDE